A novel strategy for preparing a selective back surface field of n-type emitter wrap through solar cells. (April 2017) - MA, Xiao-Bo; Zhang, Wei-Jia; Zhang, Wei; MA, Qiang; Fan, Zhi-Qiang; MA, Deng-Hao; Jiang, Zhao-Yi; Zhang, Yu-Long
Abstract: In the present study, we have developed a novel mixed co-diffusion (MCD) process by which to prepare a selective back surface field (BSF) of n-type emitter wrap through (EWT) solar cells, which combines a plasma enhanced chemical vapor deposition (PECVD) phosphorus-doped n-type microcrystalline silicon as the dopant source, with a low temperature thermal oxidation (LTO) process. Through comparison between our MCD process and a standard co-diffusion (SCD) process, a BSF with a shallow doping depth of 0.56 µm and high doping concentration of 1.9×10 20 at/cm 3 is easily obtained by the MCD process under the low temperature of 750 ℃. Therefore, the MCD process is shown to reduce the number of high temperature processes, which cannot produce dopant redistribution, and can accurately control the doping concentrations and depths of the BSF and emitter. In addition, the novel method also eliminates the boron-rich layer, which induces misfit dislocations and bulk lifetime degradation, without extra chemical treatment. Therefore, the MCD process' open circuit voltage, short circuit current density, conversion efficiency and fill factor of the solar cells are respectively increased by 7 mV, 6 mA/cm 2, 2% and 2%. These results indicate that the MCD process is a novel and potential agent for the SCD process.